Some problems in Piketty: An internal critique - Tapper, Alan (Journal of Income Distribution®, 2017)
Thomas Piketty’s evidence on wealth distribution trends in Capital in the Twenty-First Century shows that – contra his own interpretation – there has been little rise in wealth inequality in Europe and America since the 1970s. This article relates that finding to the other principal trends in Piketty’s analysis: the capital/national income ratio trend, the capital-labor split of total incomes and the income inequality trend. Given that wealth inequality is not rising markedly, what can we deduce about the putative causes that might be operating upstream? Only the capital-labor split looks like a plausible explanation of the wealth inequality trend.